EPISTEMOLOGI TAFSIR AL-AZHAR KARYA HAJI ABDUL MALIK KARIM AMRULLAH (HAMKA) (At-Tibyan, 2023)
This research aims to examine the epistemology of Tafsir Hamka in his book Tafsir al-Azhar. Tafsir al-Azhar is one of the tafsir books that has had a big influence and made many contributions in Indonesia. This is proven by the fact that this tafsir book has become a reference at State Islamic Religious Universities in Indonesia, especially at the Faculty of Ushuluddin and Sharia. This study was carried out to find out to what extent the truth of the interpretation can be tested or to what extent the truth of the interpretation can be justified. Bearing in mind, Hamka has expertise in various scientific fields such as philosophy, literature, Islamic politics, tawasuf and others. This type of research is library research with a descriptive-analytical method, and uses a historical-philosophical approach to reveal the epistemology of Hamka's interpretation in the al-Azhar commentary book. The conclusions from this research include: first, the sources of Hamka's interpretation are the Koran, Hadith, the sayings of friends, classical and modern books of interpretation, as well as reason (ratio). Second, the interpretation method used by Hamka is the tahlili method, namely interpreting the Koran in detail according to the order in the mushaf. Third, regarding the validity of interpretation, Hamka adheres to three theories of truth, namely; coherence theory, correspondence, and pragmatism. According to Hamka's coherence theory, he is consistent in building the propositions he states. And according to the correspondence theory, several verses interpreted by Hamka can be said to be in accordance with scientific facts and reality. Meanwhile, according to the theory of pragmatism, Hamka strives for al-Azhar's interpretation to contribute and provide alternative solutions for resolving various problems, especially in the social sector